REPORT OF EXPERIENCE IN THE PEDAGOGICAL RESIDENCY PROGRAM DURING REMOTE EDUCATION - Gabrielle Ferreira Santos , Ana (Revista Gênero e Interdisciplinaridade, 2021)
This paper aims to present a report of personal experience in the Pedagogical Residency Program during the COVID-19 pandemic, also known as Coronavirus. Making a brief trajectory from the beginning of the pandemic to the suspension of in-person classes, following with the implementation of remote teaching and the teaching methods that were used and their results. The work aims to present reports during the teaching follow-up period, using the descriptive methodology. During the text, ways to educate and the importance of PR will also be exposed.